Fikrah Nahdliyah Dalam Membentuk Moral Bangsa; Studi Empiris Di PWNU Jawa Timur - Husnan, Ahmad Baihaqi (khatulistiwa, 2021)
NU adopts Ahlussunah wal Jama'ah, a mindset that takes the middle path between the extremes aqli (rationalist) with the extreme naqli (scripturalist). Therefore, to reinforce identity, it was decided on a framework for the Nahdliyien which later became known as "FikrahNahdliyah". The issues raised in this study were: (1). How does Fikrah Nahdliyah's role in the process of moral formation of PWNU nation in East Java? (2). What are the features of Fikrah Nahdliyah capable of forming a moral PWNU nation in East Java? (3). What factors inhibit and support Fikrah Nahdliyah in shaping the moral PWNU nation in East Java? Answering these problems the author uses qualitative methods, using the technique of collecting data through observation, and interviews. The analysis technique I use is data reduction, data presentation, verification, and conclusion. Research Nahdlatul Ulama have a significant role in shaping the nation's morale, as evidenced by the existence of boarding schools and other institutions that are an autonomous body of the organization Nahdlatul Ulama. Results are in reform and social criticism, NU has its own perspective and methodology known as Fikrah Nahdliyah, which is a cornerstone of thinking for NU members are adhering to the principle of moderate (fikrah tawasuthiyyah), tolerance (fikrah tasamuhiyyah), reform (fikrah Islamiyah), dynamic (fikrah tathawwuriyyah) and methodological (fikrah manhajiyyah). But in society Fikrah Nahdliyah uneven implementation, as a result many of the residents of East Java who lost organizational identity, are recognized by the Regional Board of Nahdlatul Ulama, which caused a lack of socialization of the board area, branches, and twigs to the public about Fikrah Nahdliyah. The factors inhibiting and supporting Fikrah Nahdliyah are, inhibiting television shows that less educate the public, destruction of brotherhood, practical politics, and so forth. As supporters, including the actualization of values Aswaja, actualization shittah Nahdlatul Ulama, build brotherhood, community pioneers, and others.